2011
DOI: 10.1080/13803395.2011.589374
|View full text |Cite
|
Sign up to set email alerts
|

Montreal Cognitive Assessment (MoCA): Normative study for the Portuguese population

Abstract: The Montreal Cognitive Assessment (MoCA) is a brief cognitive screening instrument with good psychometric features and an excellent sensitivity in the early detection of mild cognitive decline. The MoCA was applied to a community-based sample of cognitively healthy adults (n = 650), stratified according to sociodemographic variables (age, gender, educational level, geographic region, geographic localization, and residence area), with a distribution similar to that observed in the Portuguese population. The nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
260
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 280 publications
(285 citation statements)
references
References 34 publications
18
260
4
3
Order By: Relevance
“…We excluded those previously treated with CTX and/or radiotherapy in the chest or axillary areas for other primary cancers, those that had received any treatment for breast cancer before, and those with a high probability of cognitive impairment (a score lower than 17, or lower than 16 for women over 65 years, in the Montreal Cognitive Assessment) [15].…”
Section: Patients and Settingsmentioning
confidence: 99%
“…We excluded those previously treated with CTX and/or radiotherapy in the chest or axillary areas for other primary cancers, those that had received any treatment for breast cancer before, and those with a high probability of cognitive impairment (a score lower than 17, or lower than 16 for women over 65 years, in the Montreal Cognitive Assessment) [15].…”
Section: Patients and Settingsmentioning
confidence: 99%
“…This group was selected from the database of the MoCA's normative study for the Portuguese population to match each patient on variables that were found to be predictive of the MoCA's performance (educational level and age; Freitas, Simões, Alves, & Santana, 2011), and additionally on gender. Details of the controls' recruitment procedure, inclusion and exclusion criteria, and neuropsychological assessment have been described in a previous study (Freitas et al, 2011). …”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Due to this major difference, the correction point is not entirely applicable to the Portuguese population. The norms for the Portuguese population were calculated and stratified according to different educational levels (Freitas et al, 2011).…”
Section: Materials and Neuropsychological Testingmentioning
confidence: 99%
“…Using the cut-off score from the original study, 37.3% of our normative population would have been incorrectly interpreted as cognitively impaired according to our evaluation of the population. The mean score of 26.0 (SD 2.3) was 1.0-4.2 points higher than in other normative studies [13][14][15][16][17][31][32][33], though lower than the average score of 27 for cognitively normal participants in the small original study (n = 90 healthy elderly controls). The very large normative study using data from the Dallas Heart Study (n = 2,653) included participants aged 18-85 [15].…”
Section: Discussionmentioning
confidence: 51%
“…When interpreting cognitive assessments, it is important to have population-based normative data suitable for the population on which it is being used. Several previous studies on normative data for the MoCA have included age groups below the average age of patients who are being assessed for cognitive impairment (including participants below the age of 45) [11][12][13][14][15], and some studies have derived norms based on a relatively small normal population [13,[16][17][18]. Hence, there is a need for normative data from a large population in a representative age group.…”
Section: E Borland Et Al / the Montreal Cognitive Assessmentmentioning
confidence: 99%